Analysis of the Relationship between Financial Development, Employment and Institutions on Economic Growth in WAEMU Countries - Ayivodji, Firmin; Hounsou, Rémy; Tago, Emmanuel (Archives of Business Research, 2020)
This study analyzes the relationship between financial development and economic growth on the one hand and the link between employment level and economic growth on the other hand in the context of financial liberalization. Also the question of the role of the institutional factors in the facilitation of the credit granting in the eight (08) countries of the WAEMU is approached. In doing so, strategies based on conventional fixed effects methods, with correction of Driscoll-Kraay (1998), Pooled Mean Group (PMG) of Pesaran et al. (1995, 1999) and spatial autoregressive models (SAC) are used to estimate the different equations over the period 1990-2015. The results suggest that financial development is positively associated with economic growth in WAEMU countries while an improvement in the level of employment stifles economic development. The results show that there is a positive and significant correlation between quality of democratic institutions and economic growth whatever the indicators of financial development considered except the money supply. The study recommends a strengthening of the financial development with a possible greater regularity.